2018
DOI: 10.1088/1748-9326/aabd6c
|View full text |Cite
|
Sign up to set email alerts
|

Reduced Urban Heat Island intensity under warmer conditions

Abstract: The Urban Heat Island (UHI), the tendency for urban areas to be hotter than rural regions, represents a significant health concern in summer as urban populations are exposed to elevated temperatures. A number of studies suggest that the UHI increases during warmer conditions, however there has been no investigation of this for a large ensemble of cities. Here we compare urban and rural temperatures in 54 US cities for 2000-2015 and show that the intensity of the urban heat island, measured here as the differen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
58
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 98 publications
(66 citation statements)
references
References 32 publications
8
58
0
Order By: Relevance
“…ΔT 2 can be 4°C larger in Phoenix during pre-and post-heat wave periods, leaves a large uncertainty on the synergistic interaction between future climate and UHI under heat waves. A recent study (Scott et al 2018) compared daily minimum air temperatures in 54 US cities for 2000-2015 and suggested that UHI reduces under warmer conditions. It also looked at 15 hottest nights during 2000-2015 and found weaker UHIs during heat waves.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…ΔT 2 can be 4°C larger in Phoenix during pre-and post-heat wave periods, leaves a large uncertainty on the synergistic interaction between future climate and UHI under heat waves. A recent study (Scott et al 2018) compared daily minimum air temperatures in 54 US cities for 2000-2015 and suggested that UHI reduces under warmer conditions. It also looked at 15 hottest nights during 2000-2015 and found weaker UHIs during heat waves.…”
Section: Resultsmentioning
confidence: 99%
“…It also looked at 15 hottest nights during 2000-2015 and found weaker UHIs during heat waves. Based on the results, Scott et al (2018) suggested that the synergistic interaction between heat wave and UHI found by Li and Bou-Zeid (2013) is atypical. Schatz and Kucharik (2015) showed that in Madison, UHI estimated from daily maximum air temperature shows a much clearer increasing trend than UHI from daily minimum air temperature.…”
Section: Resultsmentioning
confidence: 99%
“…Others have found evidence of UHI intensification during heat waves in Madison, WI (1.8°C daytime, 5.3°C night‐time; Schatz and Kucharik, ). However, Scott et al () showed in a multi‐city, multi‐year study that in 70% of the cities analysed, rural temperatures increased faster than urban temperatures, leading to lower UHI magnitudes during warm days. This underscores the need for studies of the underlying land surface processes that determine urban temperatures during hot days and how they vary across different regions and urban forms.…”
Section: Introductionmentioning
confidence: 99%
“…Green areas are commonly more abundant in leafy suburbs, compared to built-up inner cities. More compact cities tend to increase the UHI effect (Zhou et al 2017) and consequently worsen the impact of deadly heat waves (Mora et al 2017) (even if UHIs may often be of lower magnitude under warming conditions Scott et al 2018). While the UHI effect has positive effects in winter months in cities that have considerable heating demand, the impact of heat on health is emerging as one of the key and most harmful impacts of climate change (Gasparrini et al 2017).…”
Section: Appendix: the Uhi Effectmentioning
confidence: 99%